Optimization of the heat flow by solving inverse problem in the protective layer of the TPS panel. Issue 6 (24th May 2019) - Brodzik, Łukasz; Frąckowiak, Andrzej
Abstract : Purpose: This paper aims to present the problem of heating the damaged insulation of an orbiter. Design/methodology/approach: Changes of the insulation's thermal properties, made by adding conductive material of high value of specific heat in a form of a dope to the protective layer, were examined. An iterative algorithm determining a variable of dope concentration in the material was developed. Findings: Determination of distribution of conductive material concentration was made for materials which, after verification, demonstrated the most beneficial effect on protective properties of the modified insulation layer. The problem of determining the distribution of metal filings concentration in the insulation layer of the coating belongs to inverse heat conduction problems. Originality/value: Change of properties was to enable time extension of the LI900 insulation tile heating up to the maximal temperature and, additionally, to lowering this temperature.